Gastrointestinal Peptides During Chronic Gastric Electrical Stimulation in Patients With Intractable Vomiting. Issue 8 (10th August 2017) - Meleine, Mathieu; Melchior, Chloé; Prinz, Philip; Penfornis, Alfred; Coffin, Benoît; Stengel, Andreas; Ducrotté, Philippe; Gourcerol, Guillaume
Abstract : Objectives: Gastric electrical stimulation (GES) is an alternative therapy to treat patients with intractable vomiting. A preclinical study has demonstrated the modulation of the gastrointestinal (GI) peptide ghrelin by GES but such mechanism has never been investigated in patients. The aim of this work was to assess the effect of GES on GI peptide levels in patients with intractable vomiting. Materials and Methods: Twenty‐one patients were randomized to receive either ON or OFF GES, 14 completed the study (10 ON, 4 OFF stimulation). Vomiting episodes, gastric emptying, and gastrointestinal quality of life index (GIQLI) were assessed. Gastric and blood samples were collected before and four months after the ON period of gastric stimulation. mRNA and/or peptide levels were assessed in gastric biopsies for ghrelin, leptin, and NUCB2/nesfatin‐1 and in duodenal biopsies for glucagon‐like peptide 1 (GLP‐1) and peptide YY (PYY) using RT‐qPCR and multiplex technology. Ghrelin, leptin, GLP‐1, PYY, gastric inhibitory peptide (GIP), and NUCB2/nesfatin‐1 levels also were quantified in blood samples. Results: Among clinical parameters, vomiting episodes were slightly reduced by GES ( p = 0.09). In tissue, mRNA or protein levels were not modified following chronic GES. In blood, a significant reduction of postprandial PYY levels ( p < 0.05) was observed at M4 and a reduction of NUCB2/nesfatin‐1 levels in fasted patients ( p < 0.05). Increased plasma leptin levels after GES were correlated with reduction of vomiting and improvement of GIQLI. Conclusions: GES reduces NUCB2/nesfatin‐1 levels under fasting conditions and postprandial PYY levels in patients suffering from nausea and/or vomiting refractory to pharmacological therapies.